Thale's folly eaudiobook - Gilman, Dorothy (Recorded Books, 2016)
A New Yorker becomes ensnared by the eerie drama unfolding at a derelict New England family home in this charming mystery from the author of the Mrs. Pollifax novels. At the request of his father, New York City novelist Andrew Thale tackles an odd assignment—to check out an old family property in Massachusetts, neglected since Aunt Harriet Thale's death years ago. But far from being deserted, Thale's Folly, as Andrew discovers, is fully inhabited—by a quartet of charming squatters, former "guests" of kindhearted Harriet. There is elegant Miss L'Hommedieu, Gussie the witch, Leo the bibliophile, and beautiful Tarragon, who is unlike any girl Andrew has ever met in Manhattan. Andrew is entranced by these unworldly creatures and their simple life. Yet all is not well in Thale's Folly. A thief breaks into the farmhouse, an old friend of the "family" disappears, and Andrew and Tarragon are drawn into mysteries they cannot fathom. ... "Delightful ... a suspenseful romp ... highly recommended."—Booklist